Fertilization (N and K2O) of fertirigated coffee in the first year after planting in the southern region of Minas Gerais state (Coffee Science - ISSN 1984-3909, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->Irrigated coffee production represents approximately 10% of the total area planted with coffee and 25% of Brazil’s annual production of the crop. This study aimed at determining the effects of different doses and splittings of N and K2O fertilization, applied via drip fertirigation, on growth and leaf N and K concentrations in the first year of fertilization after planting. The cultivar Catiguá MG-3 was used in a 2.50 m x 0.6 m spacing. Treatments consisted of combinations of five doses of N and K2O fertilizer ((i) 70%, (ii) 100%, (iii) 130%, (iv)160%, and (v) 190% of the recommended dose for non-irrigated coffee), two split applications ((i) four and (ii) twelve applications) and a non-irrigated control treatment that received 100% of the recommended dose in four applications during the rainy season. The experimental design was in randomized blocks with four replications in split-plots. Plots were constituted by different splitting managements and split–plots by different doses. In each split-plot eight plants, from a total of ten, were sampled. Plant growth (plant height, stem and crown diameter) was higher in the treatments that received twelve fertilizer applications and did not vary according to the fertirigation doses, but was lower in the non-irrigated control treatment. In fertirigated coffee fields in the southern region of Minas Gerais state, N and K2O doses should be reduced to 70% of the amount usually recommended for non-irrigated coffee, providing that twelve monthly applications are done.